Combined effect of low dose atorvastatin, aspirin, clopidogrel and cessation of smoking for one year on totally occluded left anterior descending coronary artery in 39-year-old obese physician: a case report - Pyar, Khin Phyu; Aung, Chan Aye; Myo, Aung Si; Htun, Ye Myat; Maung, Thant Zaw; Hlaing, Soe Win; Aung, Zar Nin Htet; Maung, Nyan Lin; Kyaw, Aung Phyoe; Oo, Min Lynn Zaw; Zar, Sai Kyaw Tay; Aung, Nay Myo; et al. (Jour Med Resh and Health Sci, 2022)
A 39-year-old physician had severe central chest pain and cardiogenic shock due to acute inferior myocardial infarction one year ago; bare metal stent was inserted into occluded right coronary artery, culprit artery. Left anterior descending artery (LAD) was found to be totally occluded too, planned for future procedure. He had multiple risk factors: high BMI 28, heavy smoking, high cholesterol 220 mg% and sedentary life style. He quit smoking after the event. He has been taking atorvastatin 10 mg, aspirin 75 mg and clopidogrel 75 mg in addition to diuretics and low dose ramipril. He could not do exercise as his effort tolerance was poor. One year later, recheck coronary angiogram revealed a good flow in right coronary artery; moreover, there was distal flow in totally occluded LAD. Therefore, bare metal stent was inserted after dilatation. Blood tests were almost the same. In this patient, spontaneous flow in totally occluded LAD was due to combined effect of low dose atorvastatin, aspirin, clopidogrel and cessation of smoking for one year; not due to exercise or weight reduction. Low dose statin and smoking cessation had effect on atheromatous plaque on LAD.